Developmental changes of N400 event related potential of a semantic category decision task and modality specific findings in patients with developmental dyslexia - Oana, Shingo; Inagaki, Masumi; Suzuki, Seiko; Horimoto, Reiko; Kaga, Makiko (No to hattatsu, 2006)
We investigated modality-specific changes in N400 event related potential using a semantic category decision task in 38 control subjects and 8 patients with developmental dyslexia. In control children under 10 years old, auditory N400 showed a negative deflection over the fronto-centro-parietal areas with substantial amplitude. Control children over 10 years old showed a similar pattern of N400 waves in a visual and an auditory-visual modality, suggesting that the visual modality becomes dominant in the late teens. Dyslexic children showed more errors on a visual than auditory modality task with poorer N400 waves for visual stimuli. However, peak latencies of N400 in an auditory-visual modality were almost the same for auditory stimuli in control children. Differences in the N400 pattern in children might reflect the fragility and reversibility of the semantic processes through stimulus modalities.